Characterization of hybrid biocomposite synthesised with multi-walled carbon nanotube for finite strain application of aerospace structures - Ismail, Khairul Izwan (2018)
Generally, synthetic-natural hybrid composites are being introduced to lessen the use of synthetic fibres in composites as well as to deal with the drawbacks of natural fibres in biocomposites. The combination of both properties, from synthetic and natural fibres, results in hybrid biocomposites with surpass properties compared to its elements. Meanwhile, the use of nano-fillers in composites, as reported, can either enhance or diminish the properties of composites, depending on several factors. Therefore, this research was intended to study the effects of multi-walled carbon nanotube (MWCNT) concentration, on the properties of hybrid biocomposites. In this study, high cost synthetic fibres, i.e. glass, carbon and Kevlar, were respectively hybridised with the natural fibre of flax. The epoxy matrix used was modified with 0%, 0.5%, 1.0%, 1.5% and 2.0% of multi-walled carbon nanotubes (MWCNTs) to fabricate five different types of composites for each hybrid combination. In terms of mechanical properties, hybrid flax-carbon biocomposites with 1.0% MWCNT exhibit the highest tensile strength, while these same hybrid combinations possess the highest flexural strength at 0.5 % MWCNT. Analysis of the thermal properties suggested that the inclusion of MWCNT lowered the thermal stability as these nanofillers enhanced the heat diffusion, thus speeding up the degradation. Comparison between the different stacking sequences of hybrid flax-carbon and flax-glass with 1% of MWCNT showed that the flax surface are penetrated by the impactor at 15 J, while the glass and carbon surfaces were both penetrated at 20 J. The higher strength residue of hybrid flax-glass compared to flax-carbon, analysed through the compression after impact testing, was in a good agreement with the less severe damage found on the flax-glass composites.